Investigating young consumer behavior towards green products. - Nguyễn, Thị Ngọc Dịu (2020)
The rapid development of economy is both an opportunity and a challenge for enterprises. For sustainable and long-term development, the organizers may need to perform appropriate strategies to meet satisfy customer needs, wants and remain great profit to the companies and minimize the negative impact on the environment. Therefore, promoting green consumption is the most important of businesses not only in Vietnam but also around the world. Moreover, there are potential signs of green consumption in the Vietnamese market as recently, 80%of consumers are willing to spend more on green, reduce plastic bags at shop sand supermarkets clean products and brands, environmental protection or modern waste processing program, etc.The study was designed to analyze the factors that influence on green purchase intention of young consumers and design improvement and expansion of sustainability consumption in Vietnam market.This study integrated three potential factors including Environmental Concern, Environmental Knowledge and Health Consciousness that influence green buying of young generation. In particular, HC is additional than previous research it may be appropriate and strongly influence on purchase intention.